The growth of the canine glioblastoma cell line D‐GBM and the canine histiocytic sarcoma cell line DH82 is inhibited by the resveratrol oligomers hopeaphenol and r2‐viniferin. (10th August 2012) - Empl, M. T.; Macke, S.; Winterhalter, P.; Puff, C.; Lapp, S.; Stoica, G.; Baumgärtner, W.; Steinberg, P.
Abstract Vineatrol®30 is a grapevine‐shoot extract, which contains resveratrol as well as considerable amounts of so‐called resveratrol oligomers such as hopeaphenol and r2‐viniferin. In this study, we analysed whether the two above‐mentioned resveratrol oligomers were able to inhibit the growth of the canine glioblastoma cell line D‐GBM and the canine histiocytic sarcoma cell line DH82, compared their potency to inhibit tumour cell growth with that of resveratrol and determined whether the induction of apoptosis via caspase 9 and 3/7 activation underlies the tumour cell growth‐inhibiting effect of hopeaphenol and r2‐viniferin. Vineatrol®30, resveratrol, hopeaphenol and r2‐viniferin inhibited the growth of D‐GBM and DH82 cells in a concentration‐dependent manner, whereby hopeaphenol and r2‐viniferin were more potent than resveratrol itself in inhibiting the growth of the canine tumour cell lines. Moreover, the anti‐proliferative effect of both resveratrol oligomers in D‐GBM cells is based on their capacity to induce caspase 9 and 3/7 activation.